2020
DOI: 10.1038/s41396-020-0589-3
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota response to helminth infection depends on host sex and genotype

Abstract: Vertebrates’ gut microbial communities can be altered by the hosts’ parasites. Helminths inhabiting the gut lumen can interact directly with their host’s microbiota via physical contact, chemical products, or competition for nutrients. Indirect interactions can also occur, for instance when helminths induce or suppress host immunity in ways that have collateral effects on the microbiota. If there is genetic variation in host immune responses to parasites, we would expect such indirect effects to be conditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 59 publications
7
45
2
Order By: Relevance
“…Our results indicate that the microbiome composition of fish exposed to S. solidus strongly depends on host genotype. In control individuals, we observed host genotype-specific constitutive differences in microbiome composition that confirm that host-based selective processes shape the organism microbiota [86][87][88], probably due to constitutive differences in immune gene expression pathways between populations [33,73,89,90]. In agreement, we found host-genotype dependent differences in the relationship between key immune genes and abundance of bacterial families, indicating that fish of different origins have developed different sensitivity to different bacterial families.…”
Section: A Host-genotype Dependent Constitutive Response To Exposure Impacts the Microbiomesupporting
confidence: 81%
See 3 more Smart Citations
“…Our results indicate that the microbiome composition of fish exposed to S. solidus strongly depends on host genotype. In control individuals, we observed host genotype-specific constitutive differences in microbiome composition that confirm that host-based selective processes shape the organism microbiota [86][87][88], probably due to constitutive differences in immune gene expression pathways between populations [33,73,89,90]. In agreement, we found host-genotype dependent differences in the relationship between key immune genes and abundance of bacterial families, indicating that fish of different origins have developed different sensitivity to different bacterial families.…”
Section: A Host-genotype Dependent Constitutive Response To Exposure Impacts the Microbiomesupporting
confidence: 81%
“…Regardless of host or parasite genotype, and regardless of the lab environment, exposure and infection by S. solidus were associated with consistent changes in the microbiome. Indeed, herein, and within Ling et al [36], a significant increase in Rhodobacteriales was found associated with exposure and infection by S. solidus. In addition, both our field study and experimental infections revealed a previously unreported increase in alpha diversity metrics and bacterial load in infected individuals.…”
Section: Both Exposure and Infection Influence The Host Microbiome Compositionsupporting
confidence: 80%
See 2 more Smart Citations
“…Here, we report evidence for covariation between hosts' gene expression and their gut microbiota, from a large sample of laboratory-bred three-spined stickleback (Gasterosteus aculeatus), a small fish native to northern temperate coastal marine and freshwater habitats. Like many vertebrates, individual stickleback harbor hundreds of microbial taxa (operational taxonomic units [OTUs]) in their intestines (46)(47)(48)(49). The composition of this microbiota differs dramatically between cooccurring individuals within a given natural population and between populations (between neighboring lakes, adjacent lakes and streams, or marine versus freshwater [ (46)(47)(48)(50)(51)(52)).…”
mentioning
confidence: 99%